FAKTOR-FAKTOR PENYEBAB TERJADINYA LEUKHOREA (KEPUTIHAN): PADA REMAJA PEREMPUAN LITERATURE REVIEW - Aqiila Nafiisa Astari; Sabrina Ameria; Selsadilla; Wahyudi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Vaginal discharge (fluor albus) is a discharge from the vagina that can be normal or abnormal. In adolescent girls, vaginal discharge often occurs due to hormonal changes, poor reproductive hygiene, and psychological factors such as stress. Stress can affect the balance of estrogen, which plays a role in vaginal fluid production, potentially increasing the risk of vaginal discharge. This condition is important to consider because adolescence is a developmental stage vulnerable to emotional stress, academic pressures, and social changes that can cause prolonged stress. The high incidence of vaginal discharge in adolescents indicates the need to understand triggers, particularly stress, for early prevention. This study aims to determine the relationship between stress levels and the occurrence of vaginal discharge in adolescent girls. The discussion focuses on the link between psychological changes and the body's physiological reactions to stress, which can trigger disorders of the reproductive organs, particularly vaginal discharge.